Production of Multiple Hydrolytic Enzymes by Black Aspergilli Isolated from Date and Grape - Zehra Gulsunoglu; Meral Kilic-akyilmaz; Funda Karbancioglu-guler; Katleen Raes (Journal of Agricultural Sciences)
including cellulase, tannase and pectinase. Isolates were morphologically and molecularly identified as Aspergillus niger, Aspergillus tubingensis, Aspergillus japonicus and Aspergillus aculeatus. Isolates were screened for enzyme production ability on solid and in liquid media. Enzymatic activity was determined in the culture filtrate of liquid medium. A total of six isolates were found to produce multiple hydrolytic enzymes. The highest activity of cellulase was produced by A. japonicus ZGM4 and A. aculeatus ZGM6 as 40 and 35 U g-1 dry biomass, respectively. All the isolates exhibited high level of tannase activity in the range of 150-343 U g-1 dry biomass after 24 h of incubation. A. tubingensis ZGM5 and A. aculeatus ZGM6 were found to produce the highest pectinase activity at a level of 130 and 117 U g-1 dry biomass, respectively. In the light of these results, isolates can be used for multiple hydrolytic enzyme production in industry.